Selective toxicity of a novel antimicrobial peptide Acidocin 4356 against Pseudomonas aeruginosa and Acinetobacter baumannii in human cell-based in vitro infection models - Mahbubeh Talaee; Sima Modiri; Marzieh Rajabi; Fatemeh Saadati; Ali Akbari; Sahar Javadi; Shuaiqi Guo; Hojatollah Vali; Kambiz Akbari Noghabi (Scientific Reports)
Abstract Prior studies examined Acidocin 4356’s antibacterial and antivirulence effects against Pseudomonas aeruginosa, including cell membrane penetration abilities. Building on prior research, an in-vitro co-culture of human cells was established to evaluate the selectivity of Acidocin (ACD) by concurrently cultivating human cells and bacterial pathogens. This study evaluated the antibacterial effectiveness of ACD against Acinetobacter baumannii and Pseudomonas aeruginosa. Laser scanning confocal microscopy (LSCM) and scanning electron microscopy (SEM) revealed significant biofilm dispersion at ACD concentrations as low as 1/2 MIC. The cytotoxicity of ACD was evaluated on two human cell lines, Calu-6 and THP-1, using the MTT assay. The IC50 values were 114 µg/mL and 24 µg/mL after a 12-hour treatment duration. In a co-culture model, the IC50 increased to 118 µg/mL, showing greater resilience of THP-1 cells under these settings, mimicking in-vivo conditions. Fluorescent microscopy and flow cytometry analysis confirmed the MTT results, showing ACD’s potent antimicrobial effects and minimal toxicity to human cells, even after 12 h of treatment. Transmission electron microscopy (TEM) study revealed that normal Calu-6 cells included papillary outgrowths and microvilli, while infected cells displayed secretory vesicles, indicating an active response to P. aeruginosa infection. The present study thus serves as a critical step toward the development of an innovative therapeutic strategy targeting biofilm-associated infections.